The contribution of weather forecast information to agriculture, water, and energy sectors in East and West Africa: A systematic review - Agyekum, Thomas Peprah; Antwi-Agyei, Philip; Dougill, Andrew J. (Frontiers in Environmental Science, 2022)
The provision of timely and precise weather information could reduce the vulnerability of people to climate change risks. In this study, we conduct a systematic review to synthesize the existing evidence on weather information services for the agriculture, water, and energy sectors of East and West Africa and identify priorities for future research. This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement checklist. The review identified relevant peer-reviewed publications using ScienceDirect and Scopus databases for original research articles published in English from 2000 to 2022. After applying the eligibility criteria, 25 articles were included in the final review. The themes emerging from the articles were extracted, and a summary was provided to illustrate each theme. The review revealed that weather information studies focus more on the agriculture sector than energy production and water resource management. Users of weather information mainly accessed information related to rainfall and temperature, and the information was accessed mainly through radio, mobile phones, and television. Most of the information provided focused on generic meteorological forecasts instead of tailored impact-based forecasts. Only very few users can access, or benefit from the information produced due to poor communication and technical understanding of weather information. In addition, a lack of downscaled information, logistics, and trust hinders the uptake and use of climate information. Consequently, mainstreaming capacity-building of key stakeholders is required to promote effective adoption and strengthening of climate information services across East and West Africa. Systematic Review Registration: [website], identifier [registration number].